0597 How Do PAP Compliant Patients Prepare for Extreme Weather Events. A Survey Based Query Following Hurricane Irma. (27th April 2018) - Kwasnik, A; Castillo Pedraza, C M; Brito, Y; Abreu, A; Chediak, A
Abstract: Introduction: Our location in South Florida provides a unique opportunity to observe the influence of extreme weather (EW) conditions on individuals with obstructive sleep apnea who use positive airway pressure (PAP) therapy. To our knowledge, there is no centralized source of preparedness information specific to PAP in advance of EW events. Furthermore, there is a paucity of data to describe patient concerns and EW preparation patterns in such scenarios. In order to gauge PAP preparedness, concerns and actions of our population we developed and administered a PAP EW survey (PEWS) following Hurricane Irma (HI), a storm that impacted Miami on September 9, 2017. Methods: CMS criteria compliant PAP users were identified by a database search (609) or clinic follow-up (42) after HI. The PEWS was administered either in person by practitioners during office encounters or by telephone interview. The data was collected in September and October 2017. Results: We identified 651 patients with objective PAP use for 30–90 days before HI. Of these, 117 completed the PEWS. 56 (49%) admitted concern over PAP use before HI. PAP hurricane preparedness research was reported by 14 (12%) and 39 (33%) made special preparations including but not limited to evacuation, purchasing generators and battery packs. Post HI, 39 (33%) missed PAP for at least 1 day (mean 3.6 days) and symptom recurrence included snoring (43%), restless sleep (29%) and daytime sleepiness (29%). Missed PAP occurred predominantly from power outages and misplaced equipment during evacuation. Lack of sufficient power outlets in shelters and failure of adaptations used for religious observance were less common causes of missed PAP. Respondents identified email from providers, direction to approved websites and in person or printed education during clinic visits as desirable for future EW events. Conclusion: A significant portion of regular PAP users are concerned over continuance of treatment in the event of EW events. A centralized resource to prepare PAP users for EW events is desirable. Support (If Any): None.